The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1103/physrevb.84.195312
|View full text |Cite
|
Sign up to set email alerts
|

Positronium formation via excitonlike states on Si and Ge surfaces

Abstract: Recent experiments combining lifetime and laser spectroscopy of positronium (Ps) show that these atoms are emitted from p-Si(100) at a rate that depends on the sample temperature, suggesting a thermal activation process, but with an energy that does not, precluding direct thermal activation as the emission mechanism. Moreover, the amount of Ps emitted is substantially increased if the target is irradiated with 532 nm laser light just prior to the implantation of the positrons. Our interpretation of these data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 86 publications
4
40
0
1
Order By: Relevance
“…Since Ps is not expected to exist in the bulk of any such materials, it was assumed that Ps formation was occurring via the same thermal desorption process in all cases. However, recent experiments have shown that this is not the case: simultaneous measurements of the Ps emission yield and energy from Si and Ge surfaces has shown that while the yield does exhibit the same Arrhenius type of thermal dependence, the Ps energy is not thermal in nature [113,114]. The exact mechanism underlying this process is not yet known but the formation of an exciton-like Ps state (PsX) on the surface has been hypothesized [111], analogous to electronic surface exciton (X) formation [276].…”
Section: Ps Productionmentioning
confidence: 91%
See 3 more Smart Citations
“…Since Ps is not expected to exist in the bulk of any such materials, it was assumed that Ps formation was occurring via the same thermal desorption process in all cases. However, recent experiments have shown that this is not the case: simultaneous measurements of the Ps emission yield and energy from Si and Ge surfaces has shown that while the yield does exhibit the same Arrhenius type of thermal dependence, the Ps energy is not thermal in nature [113,114]. The exact mechanism underlying this process is not yet known but the formation of an exciton-like Ps state (PsX) on the surface has been hypothesized [111], analogous to electronic surface exciton (X) formation [276].…”
Section: Ps Productionmentioning
confidence: 91%
“…Both thermal and optical excitation result in the emission of Ps with a nearly constant energy. Indeed, in some cases the Ps energy has been observed to decrease at higher temperatures [113,114], completely ruling out a thermal desorption model. This may be due to a modification of the electronic surface energy levels when there are many electrons present.…”
Section: Ps Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…La espectroscopía de aniquilación de positrones (PAS) es una poderosa y versátil herramienta para el estudio de distintos tipos de materiales nivel nanoestructural: metales, semiconductores, polímeros ya que posee características únicas debido a su alta sensibilidad a la presencia de defectos de tamaño atómico y nanométrico tales como vacancias, aglomerados de vacancias o nanohuecos (voids) [1,3]. Asimismo, PAS posibilita la identificación y caracterización de cada uno de estos defectos siendo posible obtener, además, información experimental detallada de la estructura electrónica y atómica de la región estudiada por los positrones.…”
Section: Introductionunclassified